Mental Accounting in Household Financial Management (Study in Civil Servants of Senior High School Teachers in Sirimau District Ambon) - Micrets Agustina Silaya; Chricella Natalia Joseph; Dessy Balik; Debby Likumahua (International Journal of Science, Technology & Management, 2021)
Objectives-Financial management is the process of systematically carrying out financial resources to meet the needs of life. In financial management, a person often thinks partially, thus causing illogical use of money because of the mental accounting aspects of the individual. This research aimed to analyze mental accounting in household financial management of civil servants of senior high school teachers in Sirimau District Ambon. Methods - This research was a descriptive study. The sample in this research was civil servant of high school teachers in Sirimau District Ambon. The research was carried out by distributing questionnaires directly to the high school teacher in Sirimau district Ambon. The analysis technique used in this research is descriptive statistics using frequency distribution. Results - The research results indicate that there is a mental acoounting in household financial management. This can be seen from the behavior that tends to classify and enforce differently depending on where the money comes from. In this research, mental accounting is used as a self control in the sense that it does not have a biased effect but a good one.